PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI SISTEM PERNAPASAN DI KELAS XI SMA PGRI PRABUMULIH - Munir Munir; Erie Agusta; Beby Desty Arisandy (Bioilmi: Jurnal Pendidikan, 2017)
This study is based on the low level of students' science process skills. This is because in the learning process that takes place students are more passive role and only receive learning materials provided by the teacher. Model Problem Based Learning is a learning model that is using the problem as a benchmark, the purpose of this study was to determine the effect of the Model Problem Based Learning (PBL) on Science process skills To the material of the respiratory system in the class XI on SMA PGRI Prabumulih. This research uses quasi-experimental research (Quasi Experimental Reasearch) using descriptive quantitative data analysis techniques. The instrument used in this research is the test and performance assessment. Analysis of the data from the two classes using t-test Independen Sampel t test Analysis of the data from the two classes using t-test with independent testing samples test-t with t count> t table (2,066> 2,000), then H 0 rejected and H a accepted, which means that the model of problem based learning affects the students' science process skills, and Paired sample t-test in experimental class with the value t count <t table (-6.353 <-2.045), then Ho is rejected it means there is a difference science process skills between before and after the implementation of the learning model of problem-based learning. It was concluded that model of problem based learning It was concluded that model of problem based learning affects on the material respiratory system science process skills of students in class XI SMA PGRI Prabumulih.